SUMMER SCHOOL OF GERMAN LAW IN GERMANY (Journal of actual problems of jurisprudence, 2019)
This trip took place through personal contacts of the Dean of the law school doctor of law.N.,Professor Daulet Baydeldinov Lakovich, which signed an Agreement in the conduct andorganization of the international conference "the Ratio of foreign investment to environmentallaw " in Almaty in the project funded by the Fund "Volkswagen" Law and foreigninvestments in Azerbaijan, Kazakhstan and Russia: ratio and difference".